Muscle activity during gait-like motion provided by MRI compatible lower-extremity motion simulator. (2nd April 2016) - Ikeda, Takahiro; Matsushita, Akira; Saotome, Kousaku; Hasegawa, Yasuhisa; Matsumura, Akira; Sankai, Yoshiyuki
Abstract : This paper describes an evaluation of muscle activity of volunteers while they undergo gait-like motion in their dorsal position supported by our lower-extremity motion simulator (LoMS) that is magnetic resonance imaging (MRI) compatible. Our LoMS is designed to provide gait-like motion for a wearer in his/her dorsal position while a functional MRI measures his/her brain activity. A purpose of providing gait-like motion by LoMS is to enable a wearer in the dorsal posture to move his/her lower extremities like gait. LoMS is controlled with torque control based on predictive control method to convert the gravity effect of the dorsal posture into the caudal posture. The performance providing gait-like motion is evaluated from two viewpoints of muscle activities: bioelectrical potential (BEP) transition and inhibition of musculus soleus during the motion. There were correlation of BEP transition at iliopsoas, quadriceps femoris, musculus tibialis anterior, and musculus soleus. The inhibition during the gait-like motion provided by LoMS was similar to the inhibition during treadmill gait. The inhibition is modulated by a level of cerebellum, brainstem and spinal. Therefore, it is considered that LoMS induces the motor sensation in the level of cerebellum, brainstem, and spinal by providing the gait-like motion. Graphical Abstract: